Peningkatan Kompetensi Bahasa Inggris bagi Dosen-dosen Unma Banten melalui Pelatihan “TOEFL Strategies and Predictions” - Ade Sudirman (Universitas Mathla'ul Anwar Banten, 2020)
IMPROVEMENT OF ENGLISH LANGUAGE COMPETENCE FOR UNMA BANTEN LECTURERS THROUGH TOEFL STRATEGIES AND PREDICTIONS TRAINING. English language training activity in community service is intended to improve English language competence, especially when answering questions in the Test of English as a Foreign Language (TOEFL) for lecturers at Mathla'ul Anwar University (Unma), Banten. This training was conducted in the form of a short one-day training with 12 lecturers taking place in the Unma Banten hall. The material covered was TOEFL at glance, 12 Strategies for Listening comprehen-tones, 25 strategies for Structure and written expressions, and 6 strategies for reading comprehension. The training begins with a pre-test and ends with a post-test TOEFL questions as well as a prediction of scores and how to calculate TOEFL scores obtained by all trainees. The methods used in community service activities were lecturing, question and answer, discussion and demonstration methods. Based on observations during the community service activities, several positive results were obtained including: (1) The participants showed very high attention to the training material, (2) The participants showed a positive reaction to the material in answering the questions about the questions and how to calculate their values in the training, (3) The participants actively asked questions and revealed the problems they were experiencing. during this time and they are eager to implement strategies/skills in doing on the TOEFL problem, (4) The participants looked serious and confident in discussing the exercises on the TOEFL questions. The result of this community service is the increasing insight of Unma Banten lecturers about the TOEFL and how to answer questions and how to calculate the TOEFL score. In addition, they are more confident in using English and are motivated to learn English well.